Nové směry v elektrochemii biomakromolekul: stručný přehled a diskuse - Vacek, Jan; Novák, David; Zatloukalová, Martina (Chemické listy, 2017)
Electrochemical methods play an important role in basic physical and chemical research and are widely used for analytical purposes, today especially in the development of new sensors and in miniaturized laboratory technology, working both in a stationary and a flow-through mode. Since mid 20th century, electrochemical approaches have been applied in their full extent for biochemical and biophysical research, which led to the emergence of a new discipline called "bioelectrochemistry". This work aims to inform readers about current trends in the electrochemistry of biologically active substances; attention is given mainly on macromolecular systems. In addition to research focused on the analysis of nucleic acids and proteins, dynamic processes associated with intermolecular interactions, transporter effects and interactions of molecules with solid surfaces and membranes immobilized onto electrode surfaces are described here. The authors do not claim to provide a comprehensive overview of current knowledge. On the contrary, our work targets on selected areas of interest: the above-mentioned segments of bio¬electrochemical research are discussed and critically assessed.
Keywords: simulace molekulového dockingu; biomolekuly; biopolymery; Electrodes; bioelektrochemie; Biopolymers; elektrody; Molecular Docking Simulation; biomembrány; Electrochemical Techniques; elektrochemické techniky